2019
DOI: 10.1080/23273798.2019.1624789
|View full text |Cite
|
Sign up to set email alerts
|

Anticipating predictability: an ERP investigation of expectation-managing discourse markers in dialogue comprehension

Abstract: In two ERP experiments, we investigated how the Dutch discourse markers eigenlijk "actually", signalling expectation disconfirmation, and inderdaad "indeed", signalling expectation confirmation, affect incremental dialogue comprehension. We investigated their effects on the processing of subsequent (un)predictable words, and on the quality of word representations in memory. Participants read dialogues with (un)predictable endings that followed a discourse marker (eigenlijk in Experiment 1, inderdaad in Experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 89 publications
1
9
0
Order By: Relevance
“…The larger hit rate to seen words than false alarm rate to unseen words indicates that participants were paying attention during the experiment and remembered the words. Average d' was 1.29 (SD = 0.39, range = 0.42-2.41), which is similar in size to earlier psycholinguistic studies examining effects of predictability on word recognition (e.g., Hubbard et al, 2019;Rommers & Federmeier, 2018;Rasenberg et al, 2020). One participant was excluded from the analyses reported below because they did not use the full response scale (i.e., they only gave highconfidence responses).…”
Section: Word Recognitionsupporting
confidence: 67%
“…The larger hit rate to seen words than false alarm rate to unseen words indicates that participants were paying attention during the experiment and remembered the words. Average d' was 1.29 (SD = 0.39, range = 0.42-2.41), which is similar in size to earlier psycholinguistic studies examining effects of predictability on word recognition (e.g., Hubbard et al, 2019;Rommers & Federmeier, 2018;Rasenberg et al, 2020). One participant was excluded from the analyses reported below because they did not use the full response scale (i.e., they only gave highconfidence responses).…”
Section: Word Recognitionsupporting
confidence: 67%
“…We interpret the findings that infant contingent vocalisations did not generate N400 as indicating that the infant vocalisations were less meaningful in nature, as they were babbled phonetic syllables, and therefore no lexical access was performed. One recent study in adults using conversational speech showed an N400 effect while comparing the response to predictable versus unpredictable words ( Rasenberg et al, 2020 ). However, the lexical congruency of the contingent and non-contingent stimuli were not explicitly manipulated in the current experiment.…”
Section: Discussionmentioning
confidence: 99%
“…They found that native speakers of Dutch experienced higher processing costs after encountering an utterance with eigenlijk relative to encountering an utterance containing inderdaad "indeed", which could be ascribed to the efforts needed to revise the discourse model. Similarly, Rasenberg et al (2020), who investigated the processing of the same two discourse markers by means of two ERP experiments, found that words following eigenlijk elicited an enhanced posterior post-N400 positivity compared with words following an adverb, which, as they argue, may be potentially due to increased processing costs associated with pragmatically driven discourse updating.…”
Section: Particles and L2 Acquisitionmentioning
confidence: 95%
“…Particles in general are difficult to learn for non-native speakers (Fox Tree 2010;Foolen 2010). It could be expected that a particle such as eigenlijk is especially complex to acquire, as interpersonal markers seem to be used infrequently by non-native speakers (Buysse 2010), and eigenlijk in particular seems to induce higher processing costs for native speakers as well (van Bergen & Bosker 2018;Rasenberg et al 2020). This research will investigate whether non-native speakers of Dutch understand the two core properties of a context in which eigenlijk is appropriate, namely that (1) the context gives rise to a particular expectation and (2) the utterance containing eigenlijk forms a contrast with this contextually raised expectation (van Bergen et al 2011).…”
Section: Particles and L2 Acquisitionmentioning
confidence: 99%